An Analysis of Diversity and Leadership Practices and Their Impact on Organizational Outcomes - Nutan Mahalanabis (Journal of Management and Administration Provision, 2021)
The purpose of this research was to examine how variety and leadership styles affect business performance. According to the descriptive data, the sample included people of different sexes, nationalities, and ages. A favorable relationship between diversity and organizational outcomes was found in an examination of diversity in the workplace. Positive associations were also found between effective leadership practices like communication, strategy, and empowerment. This suggests that diverse teams may need to be led in a different way than homogenous ones, as there was a positive correlation between diversity and successful leadership practices. Findings from the research can help businesses improve their results and foster more welcoming workplaces for all employees.